Layering smart management practices to sustainably maintain rice yields and improve water use efficiency in eastern India - Chaurasiya, Asheesh; Dutta, S.K.; Singh, Ajoy Kumar; Kumar, Sanjay; Kohli, Anshuman; Homa, Fozia; Kumar, Arun; Gathala, Mahesh Kumar; Laing, Alison M. (Elsevier, 2022)
Rice in eastern India is widely cultivated using conventional management practices, including puddled transplanting (PTR) for crop establishment, which are water and energy intensive. To conserve water and maximise its efficient use, improved crop management practices must be identified which are feasible and attractive to farmers. These improved practices include dry direct seeding of rice (dDSR), improved medium-duration rice varieties and alternate wetting and drying (AWD) irrigation management. These have separately been shown to reduce the irrigation water requirement for rice cultivation while maintaining yields similar to those of traditional high yielding long-duration varieties. We conducted a field experiment over two rice-growing seasons to examine the effects on rice grain yield and water productivity of layering these improved management practices, compared to conventional PTR with traditional long-duration rice. We also assessed the usefulness of simple perforated tubes to implement AWD management in the field. dDSR reduced rice grain yield by 3–6% while requiring 23% less irrigation water over PTR. The medium-duration hybrid rice variety produced 2–4% higher grain yield under direct seeding while using 4–5% less irrigation water than the long-duration variety. AWD reduced irrigation water use by 26–52% but also reduced grain yield by 3–14%. Water use efficiency was improved by dDSR, AWD and by using medium-duration hybrid variety. Combining all three management practices reduced irrigation water use by an average of 18% while improving irrigation water productivity by 21%, without significant reduction in grain yield under shallow AWD of 10 cm depth in dDSR and upto 15 cm depth for PTR. This combination is a novel approach to sustainably improve farmers’ rice productivity. Additionally, simple perforated tubes are an effective and innovative tool for farmers to implement AWD management. Our research suggests that farmers in eastern India and similar rice-growing agro-ecologies could reduce the irrigation water applied and increase water use efficiency while maintaining rice crop productivity by combining dry direct seeding with a medium-duration rice variety under AWD irrigation management.